Իսլամը և նրա գաղափարական–քաղաքական դրսևորումները մահմեդական պետությունների քաղաքականության մեջ և միջազգային հարաբերություններում - Բայբուրդյան, Վահան («Զանգակ - 97»)
Islam is a world religion - the youngest after Buddhism and Chrislianity. Though Islam is Iradilionally thoughL lo be widesprcad in countries of the Near and Middle East and North Africa, it effectively has a present-day ränge from the Atlantic Ocean to the Pacific. Analysts rcport a growing world-scale impact of Islamic states on global events.
Keywords: Կրոն; Իսլամ